2021
DOI: 10.3390/agronomy11081473
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Electrostatic Field to Improve Soybean Seed Germination in Organic Production

Abstract: Soybean production in the system of organic agriculture is not very demanding, and this has been well documented both through experimental results and commercial production. However, one of the biggest problems in organic production is the lack of adequate pre-sowing treatments. Therefore, the aim of this study was to examine the effect of the electrostatic field. This is a physical treatment that was first used for seed treatment in the 18th century but has mostly been neglected since then. Seeds of five soyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…During seed germination [11,12] , water plays an important role in maintaining the functioning and activity of seeds [13] . The state and distribution of water can affect the catalytic functions of various enzymes [14,15] , which in turn can alter the metabolic rates of biological macromolecules, such as carbohydrates, starch, lipids, and proteins, consequently [16] , affecting seed germination and emergence rates [17][18][19][20][21] . Research on the patterns of changes in the internal enzymes of seeds treated with HV-PEF has been conducted extensively and has produced remarkable results.…”
Section: Introductionmentioning
confidence: 99%
“…During seed germination [11,12] , water plays an important role in maintaining the functioning and activity of seeds [13] . The state and distribution of water can affect the catalytic functions of various enzymes [14,15] , which in turn can alter the metabolic rates of biological macromolecules, such as carbohydrates, starch, lipids, and proteins, consequently [16] , affecting seed germination and emergence rates [17][18][19][20][21] . Research on the patterns of changes in the internal enzymes of seeds treated with HV-PEF has been conducted extensively and has produced remarkable results.…”
Section: Introductionmentioning
confidence: 99%
“…The survey indicates a trend of studies related to the application of biological products in the seed, microorganisms isolated from the soil with rooting and nutrient-fixing action, promoting plant growth (PGPR) and their respective effects on germination, emergence, and seedling performance under ideal conditions or some type of environmental stress (Gregorio et al, 2017;Nazari et al, 2019;Khomari et al, 2018;Queiroz Rego et al, 2018;Tavanti et al, 2020;Abati et al, 2020;Paul and Rakshit, 2021;Sheteiwy et al, 2021). The studies grouped by physical treatments revealed the potential of new technologies such as electromagnetic field, laser, and the use of plasma to treat the seed or treat the water in which the seed will be soaked (Asghar et al, 2017;Kataria et al, 2017;Porto et al, 2018;Michalak et al,2019;Foroughbakhch et al, 2019;Pérez-Pizá et al,2019;Švubová et al, 2021;Mamlic et al, 2021).…”
Section: Technologies Used In the Treatment Of Soybean Seedsmentioning
confidence: 99%
“…Among them, the high-voltage electrostatic field treatment of seeds based on electromagnetobiology has triggered much research. Relevant studies have shown that: Reasonable electric field strength and polarisation treatment time can improve crop germination and seedling quality 10 13 . Altering endogenous hormone levels during seed germination 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%